2013
DOI: 10.1515/bmc-2012-0052
|View full text |Cite
|
Sign up to set email alerts
|

Free radical-mediated cytosine C-5 methylation triggers epigenetic changes during carcinogenesis

Abstract: The methylation of the C-5 position of deoxycytidine (dC) in the promoter regions of tumor suppressor genes is often observed in cancer cells. We found that various environmental agents, as well as endogenous compounds such as methionine sulfoxide (MetO), generate methyl radicals and modify dC to form 5-methyl-dC in DNA in vitro. We confirmed that both DNA methylation and cancer incidence in the liver were increased by the administration of MetO to oxidatively stressed mice. In this review, we summarize previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In particular, spontaneous 5-methylcytosine methylation[8] and demethylation[9] are relevant to humans.…”
Section: Entropic Drivers Of Agingmentioning
confidence: 99%
“…In particular, spontaneous 5-methylcytosine methylation[8] and demethylation[9] are relevant to humans.…”
Section: Entropic Drivers Of Agingmentioning
confidence: 99%
“…They tend to have hypomethylation overall, but hypermethylation in some genes in tumors. 33 In this study, the promoter DNA methylation levels of IL-4 and IFN-γ were found to be abnormal with contrary to mRNA expression. The results in this study also showed the decrease of genome-wide methylation rate (5-mC%) in rats' lung tissues in the PM 2.5 exposure group.…”
Section: Discussionmentioning
confidence: 53%
“…Global hypomethylation and regional hypermethylation are common mechanisms of aberrant expression of gene. They tend to have hypomethylation overall, but hypermethylation in some genes in tumors 33 . In this study, the promoter DNA methylation levels of IL‐4 and IFN‐γ were found to be abnormal with contrary to mRNA expression.…”
Section: Discussionmentioning
confidence: 55%
“…A general scheme of methyl radical formation and dCyd methylation under oxidative stress conditions is shown in Fig. 15 [ 67 , 68 ]. Endogenous compounds such as MetO, induced by smoking, inflammation and aging, can generate methyl radicals under oxidative stress conditions.…”
Section: Introductionmentioning
confidence: 99%